2003
DOI: 10.1101/gr.1386204
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Detection and Isolation of DNA Variants Using Stabilized RecA-Coated Oligonucleotides

Abstract: Several genome resequencing strategies have been developed to detect genetic variation in populations and correlate diversity with phenotypic consequences. Commonly used methods of detecting single nucleotide polymorphisms (SNPs) use PCR amplification and indirect analysis, which can create template biases and enable user contamination. Here we present a novel assay to detect and isolate DNA variants using stabile nanostructures formed directly on duplex DNA. The assay incorporates the well-established RecA-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Once bound and annealed, the ssODN forms a three‐stranded heteroduplex with the target site. Overexpression of genes such as RAD52, RAD54, RECA, and RAD51, all of which are involved in promoting the pairing process, has been shown to enhance gene correction 29–35. Furthermore, the presence of homologous recombination repair (HRR) proteins enhances repair in bacteria, yeast, and mammalian systems,29, 31, 32, 36–39 supporting a role for conventional DNA pairing activity in the ODN‐mediated repair reaction.…”
Section: Cellular Responses Impact Gene Repair Directly and Indirectlymentioning
confidence: 99%
“…Once bound and annealed, the ssODN forms a three‐stranded heteroduplex with the target site. Overexpression of genes such as RAD52, RAD54, RECA, and RAD51, all of which are involved in promoting the pairing process, has been shown to enhance gene correction 29–35. Furthermore, the presence of homologous recombination repair (HRR) proteins enhances repair in bacteria, yeast, and mammalian systems,29, 31, 32, 36–39 supporting a role for conventional DNA pairing activity in the ODN‐mediated repair reaction.…”
Section: Cellular Responses Impact Gene Repair Directly and Indirectlymentioning
confidence: 99%
“…Attempts have been made to make the structure stable enough to withstand various subsequent manipulations (Fujiwara et al 1998a,b;Potaman et al 2002;Roulon et al 2002). Recently, Rice et al (2004) reported that a D-loop formed with RecA protein is stabilized by converting it to a stable double D-loop.Using a different approach, we have devised a method to stably mark specific sequences in double-stranded DNA molecules by converting a RecA-mediated triple-stranded structure to a stable one by use of a second deoxyoligonucleotide (a splint oligonucleotide), to which the first probing oligonucleotide is aligned to covalently ligate itself. The resultant regional multi-(possibly quintuple) strand structure is stable and easily detectable by various means, including observation by scanning probe microscopy such as atomic force microscopy (AFM).…”
mentioning
confidence: 99%
“…Attempts have been made to make the structure stable enough to withstand various subsequent manipulations (Fujiwara et al 1998a,b;Potaman et al 2002;Roulon et al 2002). Recently, Rice et al (2004) reported that a D-loop formed with RecA protein is stabilized by converting it to a stable double D-loop.…”
mentioning
confidence: 99%